ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT PENGEMBALIAN KREDIT PENGUSAHA KECIL PADA PROGRAM KEMITRAAN (Studi Kasus: PT PLN (Persero) Distribusi Jawa timur Area Malang) - Nastiti, Anggri; Saraswati, Erwin (Jurnal Ilmiah Mahasiswa FEB, 2013)
This research is aimed to analyze the determinants of loan repayment rate on small medium enterprises that assisted by partnership program of PT. PLN (Persero) Malang. Loan amount, net income, business experience, debiturâ€™s age, family members, education and other income are used as variables of research. This study selects 40 small medium enterprises by using nonprobability sampling (purposive sampling method). These research data were analyzed using crosstabulation and multiple linear regression. The result shows that net income has positive effect on loan repayment rate. Â  Key Words: PKBL, Coporate Social Responsibility, Net Income